1993
DOI: 10.1038/362849a0
|View full text |Cite
|
Sign up to set email alerts
|

Thymocyte apoptosis induced by p53-dependent and independent pathways

Abstract: Death by apoptosis is characteristic of cells undergoing deletion during embryonic development, T- and B-cell maturation and endocrine-induced atrophy. Apoptosis can be initiated by various agents and may be a result of expression of the oncosuppressor gene p53 (refs 6-8). Here we study the dependence of apoptosis on p53 expression in cells from the thymus cortex. Short-term thymocyte cultures were prepared from mice constitutively heterozygous or homozygous for a deletion in the p53 gene introduced into the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

60
1,166
8
18

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,152 publications
(1,257 citation statements)
references
References 22 publications
60
1,166
8
18
Order By: Relevance
“…If p53 is mutated or inactivated in some manner, the apoptotic response is not activated and cell proliferation is allowed. Analysis of cells and tissues of p53-null mice has shown that functional p53 is necessary for DNA damage-induced apoptosis of cortical thymocytes (Clarke et al, 1993), myeloid progenitor cells (Lotem and Sachs, 1993), marrow preB cells (Strasser et al, 1994), quiescent peripheral B and T lymphocytes (Strasser et al, 1994), keratinocytes (Ziegler et al, 1994) and small intestine cells .…”
Section: Role Of P53 In Growth Arrestmentioning
confidence: 99%
“…If p53 is mutated or inactivated in some manner, the apoptotic response is not activated and cell proliferation is allowed. Analysis of cells and tissues of p53-null mice has shown that functional p53 is necessary for DNA damage-induced apoptosis of cortical thymocytes (Clarke et al, 1993), myeloid progenitor cells (Lotem and Sachs, 1993), marrow preB cells (Strasser et al, 1994), quiescent peripheral B and T lymphocytes (Strasser et al, 1994), keratinocytes (Ziegler et al, 1994) and small intestine cells .…”
Section: Role Of P53 In Growth Arrestmentioning
confidence: 99%
“…We first examine the relationship of Cdk5 to the p53-mediated signaling pathway. [43][44][45] p53 may mediate mitochondrial cell death signaling through the elevation of the level of reactive oxygen species, 46 while oxidative stress can stimulate Cdk5 activity by inducing an upregulation of p35 in human neuroblastoma IMR-32 cells. 47 Reactive oxygen species (ROS) are instrumental in a number of neurodegenerative disorders where Cdk5 is activated.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] This resistance is most likely due to the fact that cells without wt-p53 delay or are unable to initiate apoptosis. 7,11,12 In fact, administration of Ad-p53 with cis-diamminedichloroplatinum(II) (CDDP) induced tumor regression as well as apoptosis in p53-deleted human lung tumors that were grown as subcutaneous xenographs in nu/nu mice. 13 On the basis of these findings, gene therapy against p53-mutated NSCLC has started.…”
mentioning
confidence: 99%